Rheological characteristics of polymer modified and aged bitumens - Airey, Gordon (1997)
The demands on asphalt pavements, as a result of the growth in traffic volumes, traffic loads and tyre contact pressures, has resulted in an increased interest in the use of modified bitumens, particularly over the last ten years. Of the various types of modified and specialised binders that are available worldwide, polymer modified bitumens (PMB’s) have tended to be the most popular. Polymer modification significantly alters the rheological characteristics of the binder, thereby requiring the use of fundamental rheological testing methods rather than empirical methods, to provide an indication of the performance of the binder and subsequently the asphalt mixture.